Development of the methodical approach to the formation of a competitiveness strategy Bilgorod-Dnestrovskiy sea trading port - Shyriaieva, Liudmyla; Girina, Olga; Bakriev, Maxim (Technology audit and production reserves, 2017)
The object of research is the process of forming directions of increasing the competitiveness of ports, which is the result of the interaction of all elements of their production system and the external environment of providing port services. The article proposes to start the formation of a competitive strategy for the calculation of market shares of ports and the establishment of priority competitors on the basis of separation from the whole complex of those that are in close proximity to the port or have a significant impact on its activities. In the process of development of a competitive strategy of the port, it is expedient to allocate the goods which have the greatest weight in the structure of cargo turnover of the port. Such goods for port of Bilhorod-Dnistrovskyi in 2016–2017 years are timber (89.61–59.15 %) and grain (1.28–10.61 %).The share of port of Bilhorod-Dnistrovskyi for timber in the structure of the Ukraine’s ports is rather significant and overwhelming (67.76 %). Thus, the main factor in the competition of the port is not only the quality of port services, but its accessibility to internal transport systems, the development of cross-border rates of practice. The paper proposes a systematic approach to substantiate the competitive strategy of a seaport using an economic-mathematical model of cargo distribution between ports in the process of forming cargoes delivery schemes from senders to consumers. Mathematical model of the problem in the general form and the results of calculations of a control example for substantiation of the competitive strategy of the sea trading port of Bilhorod-Dnistrovskyi are presented in the article. The effect in the transport system is achieved by saving expenses from transportation and handling of cargoes in the amount of 1010 thousand UAH. It can be concluded that the use of the system approach allows obtaining the synergy effect in achieving the optimal strategy of competitiveness of the port infrastructure of the region. It is proposed to determine the optimal cargo turnover of ports in condition of optimal organization of their work. The method of modeling the entire transport system for the delivery of cargoes through the sea ports of transshipment can be the basis of state management in Ukraine of regional seaports competitiveness